Islamic Educational Leadership in the Digital Age - Fildya Rizki; Junaidi Junaidi (Early Publishing, 2026)
The rapid development of digital technology has significantly influenced various aspects of education, including Islamic educational leadership. This study aims to analyze the concept of Islamic educational leadership in the digital era, identify the challenges faced by educational leaders, and examine adaptive and innovative leadership strategies in integrating technology with Islamic values. This research employed a qualitative approach using the library research method. Data were collected from scientific journals, books, and relevant literature published within the last ten years. The data were analyzed using content analysis techniques through data reduction, data presentation, and conclusion drawing. The findings indicate that Islamic educational leadership in the digital era requires adaptive, innovative, and visionary leadership characteristics. Educational leaders are expected to effectively utilize digital technology while maintaining Islamic moral and spiritual values. The study also found several major challenges, including low digital literacy among educators, uncontrolled information flow, limited technological infrastructure, and declining social interaction among students. However, digital technology also provides opportunities to improve the quality of Islamic education through online learning platforms, digital learning media, and technology-based Islamic educational content. This study contributes to the development of knowledge by emphasizing the importance of transformational leadership in managing digital transformation within Islamic education institutions. Therefore, Islamic educational leaders should strengthen digital competence, encourage educational innovation, and maintain Islamic values to achieve effective and balanced educational goals in the digital era.